Grandma in blue with red hat - Menchin, Scott (Abrams Books for Young Readers, 2015)
After his teacher says that anything can be in an art exhibition, and his fellow students give myriad reasons why something might belong in a museum, a child offers his special grandmother as an exhibit but when the curator cites a rule against accepting grandmas, the child has a better idea.